Changes in Students’ Perceptions and Technology Acceptance in Science Education: Implementing Canva in the Context of the Digital Divide - Syahriyanti, Mita; Susanti, Nova; Amanah, Siti; Sofyan, Sofyan; Afrizal, Afrizal (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study examines changes in students’ perceptions and technology acceptance in science education following the implementation of Canva in a school characterized by limited digital access. Grounded in the TAM, the research positions perception as a mediating construct linking digital media use to learning experience quality within a digital divide context. A descriptive pre–post survey design was employed involving 41 seventh and eighth-grade students at a public junior secondary school. Data were collected using a Likert-scale questionnaire administered before and after the integration of Canva into science instruction. Descriptive statistical analysis was conducted to compare mean scores across the two measurement phases. The findings indicate a substantial positive shift in students’ perceptions after the implementation of Canva, particularly in perceived usefulness, perceived understanding of abstract concepts, and affective engagement. These results suggest that exposure to structured visual and multimodal learning materials may enhance students’ acceptance of educational technology, especially in contexts where prior access to digital tools is limited. The study contributes theoretically by extending discussions on perception and technology acceptance within underrepresented educational settings affected by the digital divide. Methodologically, it demonstrates the relevance of pre–post descriptive approaches for capturing perceptual shifts in small-scale contexts. However, the study is limited by its reliance on self-reported data and the absence of inferential statistical testing. Future research is recommended to employ longitudinal or quasi-experimental designs and to integrate measures of academic achievement to better understand the long-term impact of digital media implementation in science education.